Analisis Kondisi Sumber Daya Mineral Brown Canyon Semarang - Dewi, Clara Angelina Kusuma; Purwandari, Alberta Kristi; Maharani, Desi Febrina; Divina, Maria Beneficia; Ismail, Amrizarois (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Natural resources (SDA) are wealth that not every country in the world has. Natural Resources are divided into several parts according to their classification, including Mineral Resources. Mineral Resources are natural resources that contain minerals and mining materials that have economic value. The materials contained therein are usually used as high-value production materials, this is what causes mineral resources to sometimes be used inefficiently. One of the mineral resources in Indonesia is in Central Java Province, precisely in the city of Semarang, which is commonly known as